Synthesis of Electrospun TiO2 Nanofibers and Characterization of Their Antibacterial and Antibiofilm Potential against Gram-Positive and Gram-Negative Bacteria - Mohammad Azam Ansari; Hani Manssor Albetran; Muidh Hamed Alheshibri; Abdelmajid Timoumi; Norah Abdullah Algarou; Sultan Akhtar; Yassine Slimani; Munirah Abdullah Almessiere; Fatimah Saad Alahmari; Abdulhadi Baykal; It-Meng Low (Antibiotics, 2020)
Recently, titanium dioxide (TiO2) nanomaterials have gained increased attention because of their cost-effective, safe, stable, non-toxic, non-carcinogenic, photocatalytic, bactericidal, biomedical, industrial and waste-water treatment applications. The aim of the present work is the synthesis of electrospun TiO2 nanofibers (NFs) in the presence of different amounts of air–argon mixtures using sol-gel and electrospinning approaches. The physicochemical properties of the synthesized NFs were examined by scanning and transmission electron microscopies (SEM and TEM) coupled with energy-dispersive X-ray spectroscopy (EDX), ultraviolet-visible spectroscopy and thermogravimetric analyzer (TGA). The antibacterial and antibiofilm activity of synthesized NFs against Gram-negative Pseudomonas aeruginosa and Gram-positive methicillin-resistant Staphylococcusaureus (MRSA) was investigated by determining their minimum bacteriostatic and bactericidal values. The topological and morphological alteration caused by TiO2 NFs in bacterial cells was further analyzed by SEM. TiO2 NFs that were calcined in a 25% air-75% argon mixture showed maximum antibacterial and antibiofilm activities. The minimum inhibitory concentration (MIC)/minimum bactericidal concentration (MBC) value of TiO2 NFs against P. aeruginosa was 3 and 6 mg/mL and that for MRSA was 6 and 12 mg/mL, respectively. The MIC/MBC and SEM results show that TiO2 NFs were more active against Gram-negative P. aeruginosa cells than Gram-positive S. aureus. The inhibition of biofilm formation by TiO2 NFs was investigated quantitatively by tissue culture plate method using crystal violet assay and it was found that TiO2 NFs inhibited biofilm formation by MRSA and P. aeruginosa in a dose-dependent manner. TiO2 NFs calcined in a 25% air-75% argon mixture exhibited maximum biofilm formation inhibition of 75.2% for MRSA and 72.3% for P. aeruginosa at 2 mg/mL, respectively. The antibacterial and antibiofilm results suggest that TiO2 NFs can be used to coat various inanimate objects, in food packaging and in waste-water treatment and purification to prevent bacterial growth and biofilm formation.